Tremendous Performance Manganese Oxide Via Coprecipitation Method for Degradation of Palm Oil Mill Effluent - Prasetya, Prasetya; Muhdarina, Muhdarina; Saputra, Edy; Awaluddin, Amir (Photon: Jurnal Sain dan Kesehatan, 2024)
Increased production in industries tends to increase burden and complexity of waste produced. For this reason, it was necessary to develop materials that have good degradation capabilities and into environmental products. In this research, the MnO2 has been synthesized using the strategy of coprecipitation and reducing agents. The as-synthesized MnO2 is then used for the degradation of methylene blue. The results of this study indicate that different strategy of coprecipitation and reducing agents produce different MnO2 and has unique properties as nano-hierarchical microstructure. Using citric acid as a reducing agent results in a hierarchical structure of α-MnO2 and Mn2O3, while oxalic acid produces a hierarchical structure of β-MnO2 and Mn2O3. To optimize the degradation of Palm Oil Mill Waste which contains a high concentration of pollutants, it still needs to be improved. From the parameters pH, chemical oxygen demand, oil & grease, and total suspended solids, the best degradation efficiency of each parameter was achieved at pH 8.8, 16.3%, 43.5% and 56.6%.